Silence as a Specific Kind of Communication in Legal Discourse - Kowalczyk, Joanna (Respectus Philologicus, 2020)
The article is devoted to the description of modifying reality through non-verbal speech acts. The subject of the study are non-verbal signs referring to the category of legal communication. This study included acts of legal communication that are expressed or can be expressed using various forms of silence. The first aim of the study was to determine whether silence can be classified as a speech act in the strict sense. The secondary aim was to determine the usefulness of silence in legal communication. The methodological basis of the analysis was the assumptions of pragmatism in the approach of W. James and the concept of performative acts of speech by J. L. Austin.
Keywords: silence; legal language; institutional discourse